Real effects of bank capital regulations: Global evidence - Yota D. Deli; Iftekhar Hasan (Bank of Finland, 2017)
We examine the effect of the full set of bank capital regulations (capital stringency) on loan growth, using bank-level data for a maximum of 125 countries over the period 1998-2011. Contrary to standard theoretical considerations, we find that overall capital stringency only has a weak negative effect on loan growth. In fact, this effect is completely offset if banks hold moderately high levels of capital. Interestingly, the components of capital stringency that have the strongest negative effect on loan growth are those related to the prevention of banks to use as capital borrowed funds and assets other than cash or government securities. In contrast, compliance with Basel guidelines in using Basel- and credit-risk weights has a much less potent effect on loan growth.
URN:NBN:fi:bof-201708111507
Keywords: G21; G28; E6; O4; 330